INSEMINASI DAN BAYI TABUNG - Abdul Wahab Syakhrani; Rahniatul Jannah; Raudatunnisa Raudatunnisa; Risa Amelia; Sapiah Sapiah (Jurnal Kesehatan, 2023)
Artificial insemination or IVF means a method to help fertile couples who experience difficulties in fertilizing a woman's egg cells by a man's sperm cells. To carry out artificial insemination (al-talqih al-Sina'iyah), a husband and wife who want to get pregnant are expected to always consult a doctor as to whether they can inseminate/be fertilized to produce offspring or not. Many people actually have sperm or ovum that is quite fertile, but cannot fertilize or be fertilized because there are abnormalities in their reproductive organs, for example the Fallopian Tubes are narrowed or the sperm emission is always weak, so this will hinder birth. If a case like this occurs, the doctor will try to take the woman's eggs (ovum) by means of aspiration of follicular fluid through the vagina, with a tool called "Transpajinal Transcular Ultra Sound" and sperm from the man, also taken and then combined. The cells are then stored in a culture dish for several days. This is what is called a "test tube baby", namely a baby that will be placed into a mother's womb using a device such as an injection.